2017
DOI: 10.1186/s12866-017-1056-9
|View full text |Cite
|
Sign up to set email alerts
|

XC_0531 encodes a c-type cytochrome biogenesis protein and is required for pathogenesis in Xanthomonas campestris pv. campestris

Abstract: BackgroundThe phytopathogenic Xanthomonas campestris pv.campestris is a gram-negative bacterium and the causal agent of black-rot disease of cruciferous crops. Many gram-negative bacteria possess a family of proteins, called Dsbs, which are involved in disulfide bond formation in certain periplasmic proteins. In our preliminary screening of the virulence to the plants we identified that gene XC_0531 which annotated gene dsbD of Xanthomonas campestris pv. campestris (Xcc) is related to the virulence to the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In brief, DsbA protein transfers its disulfide bond to newly synthesized proteins and is reoxidized back to its active oxidized state by DsbB, while DsbC rearranges the misfolded proteins and is maintained in its active state form by DsbD (27,28). Although there is an unexpected diversity in the mechanisms of disulfide bond formation (29,30), the Dsb system appears to have critical roles in copper resistance in various bacterial species (24,25,(31)(32)(33)(34)(35), including Pseudomonas aeruginosa (36), a notorious human pathogen that causes more than 10% infections in most hospitals (37) and is among the microorganisms for which there is an urgent need for novel antibiotics (38).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, DsbA protein transfers its disulfide bond to newly synthesized proteins and is reoxidized back to its active oxidized state by DsbB, while DsbC rearranges the misfolded proteins and is maintained in its active state form by DsbD (27,28). Although there is an unexpected diversity in the mechanisms of disulfide bond formation (29,30), the Dsb system appears to have critical roles in copper resistance in various bacterial species (24,25,(31)(32)(33)(34)(35), including Pseudomonas aeruginosa (36), a notorious human pathogen that causes more than 10% infections in most hospitals (37) and is among the microorganisms for which there is an urgent need for novel antibiotics (38).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome c -type biogenesis protein has been reported to protect black rot disease caused by phytopathogenic Xanthomonas campestris pv. campestris from cruciferous crops ( Chen et al., 2017 ); however, the effect of the gene on FHB requires further research. Two proteins, diacylglycerol kinase and alpha-galactosidase, were located near the FHB QTL Qfhb.spa-6A.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some KB-dependent RhpR-regulated genes not only were involved in metabolic pathways but also had certain effects on virulence. In Xanthomonas campestris , the c -type cytochromes contribute to the EPS production and extracellular enzyme activities to enhance virulence ( 54 ). In Staphylococcus aureus , HemB leads to the production of α-hemolysin, protein A, and thermonuclease to maintain virulence ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%